وقفات منهجية في حياة الشيخ السهارتفوري و آثاره - Haq, M. (Universiti Sains Islam Malaysia, 2024)
Sheikh Khalil Ahmed bin Majid Ali Ansari Al-Sahrnpuri, a famous religious as well as a senior Hadith scholar (Mohaddith) in the Indian sub-continent. His lineage from his father side is assumed to be linked with the famous companion of the Prophet Muhammad (pbuh) Abu Ayyub al-Ansari. From mother side, he is also assumed to be linked to Abu Bakr Siddiq, may Allah be pleased with him. Sheikh Al-Sahrnpuri was born in ''Nanuta'' under the district of ''Sahrnpur'' in India in 1269 A.H. corresponding with 1849 A.D. He graduated from University Pakistan in 1288 A.H. During his study life he learned from a lot of seniors sheikhs and scholars of India and Pakistan. He performed pilgrimage (Hajj) seven times, and during his trips to Makkah he met many scholars of Makkah and Madinah, and attend a lot of lecturers there and heard from them Hadith and finally obtained degree certificate which is popularly known as ''izazah'' on most books of Hadith. Sheikh Al Sahrnpuri devoted all his lift to serve Islam and teaching Islamic sciences, especially Hadith and its sciences. He has a long history of teaching sunnah, reviewing it as well as editing and explaining it. One of his famous writings is ''Bazlul mazhud fi halle Sunan Abi Dawood'' which is considered as one of the best explanations for the book ''Sunan'' of Imam Abi Dawood. Sheikh Al Sahrnpuri died at the age of seventy-seven 77 years, in 1926 A.D and he was buried in Baqi cemetery in the holy city Madina.